Multielement study in the drainage sediments of a part of Lesser Himalaya, central Nepal - Jnawali, B. M (Journal of Nepal Geological Society, 1981)
Distribution of different elements from 183 regional stream sediment samples representing 600 Km2 of Chitwan-Dhading Districts (Toposheet 72A/14) has been described. The study of inter-element relationships demonstrated positive correlation among Cu, Pb & Zn. Arsenic Sb & Bi correlations are found to be positive except that Bi & Sb exhibit antipathetic relation, the former showing affinity towards granite in contrast to the latter, which was virtually absent in anomalous amount over granites. A close association of As with Cu, Pb & Zn anomalies suggest that As could be used as a pathfinder for basemetal mineralization. Regression analysis was used to study the effect of secondary hydroxides of Fe, Mn & Ni on Cu & Zn dispersion, and that of K on Sn & Pb dispersion. The only significant variance explained was Fe on regression of Cu, which was attributed to primary coherence of Cu with Fe probably in chalcopyrite or mafic minerals. The geochemical associations found in stream sediments reflect primary environment and secondary processes in surficial condition modify these very little.